2020
DOI: 10.3390/pharmaceutics12020172
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Tablets (Printlets) with Braille and Moon Patterns for Visually Impaired Patients

Abstract: Visual impairment and blindness affects 285 million people worldwide, resulting in a high public health burden. This study reports, for the first time, the use of three-dimensional (3D) printing to create orally disintegrating printlets (ODPs) suited for patients with visual impairment. Printlets were designed with Braille and Moon patterns on their surface, enabling patients to identify medications when taken out of their original packaging. Printlets with different shapes were fabricated to offer additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(84 citation statements)
references
References 63 publications
2
81
0
1
Order By: Relevance
“…Previous studies have demonstrated the potential of 3D printing to tailor oral medicines to individual patients [56] , [57] , [58] , [59] , and the feasibility of this technology to prepare tailored medicines in a hospital setting [35] . In the present study, we have investigated the potential of SSE 3D printing for the development of customised lipid-based suppositories with different sizes and containing a specific dose of drug.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated the potential of 3D printing to tailor oral medicines to individual patients [56] , [57] , [58] , [59] , and the feasibility of this technology to prepare tailored medicines in a hospital setting [35] . In the present study, we have investigated the potential of SSE 3D printing for the development of customised lipid-based suppositories with different sizes and containing a specific dose of drug.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a low-cost, open source ultrasound-based navigational support system in the form of a 3-D printable wearable bracelet has been demonstrated to allow people with vision loss to navigate, orient themselves in their surroundings and avoid obstacles when moving. Similarly, research has already shown the efficacy of 3-D printing to create orally disintegrating printlets (ODPs), suitable for patients with visual impairment, with Braille and Moon patterns on their surface, enabling patients to identify medications when taken out of their original packaging [103]. Students may start printing learning aids and Braille labels for peers, but as they become more technically sophisticated, fabricating ultrasound-based navigational aids from open-source plans or ODPs is possible and no longer economically inaccessible.…”
Section: Overall Economics and Advanced Applicationsmentioning
confidence: 99%
“…To date, although only a few papers related to the production of SODFs by SLS have been issued [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], they demonstrated clearly that it is possible to manufacture oral medicines with a sintering machine using different pharmaceutical thermoplastic polymers (copovidone, cellulose derivatives and Eudragit ® ). These contributions distinctly highlight the most important benefit that SLS could have in pharmaceutical manufacturing: its ability to create more or less porous forms by modulating the printing parameters and hence control the drug release from the printed SODFs.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that although all the aforementioned work was conducted with SLS machines that use a blue diode laser, none of the evaluated polymers absorbed at the wavelength of the laser. Therefore, a colorant e.g., “Candurin ® ” was added to enhance the absorbance and allow the sintering process [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Nonetheless, the majority of commercially available SLS printers use a different laser beam, which is the carbon dioxide (CO 2 ) laser beam (λ = 10.6 μm).…”
Section: Introductionmentioning
confidence: 99%